Pharmacokinetics of cefotiam and cefsulodin after simultaneous administration to patients with impaired renal function. - Lecaillon, J B (1984)
The possible influence of the concomitant administration of cefotiam and cefsulodin on their respective pharmacokinetics was studied in 15 patients with renal insufficiency and 10 anuric patients. Linear relations were found between the clearance of creatinine and the total clearance, as well as the renal clearance, of each drug. These relations for each cephalosporin were not significantly different from previous results obtained after separate administration. In hemodialyzed patients, the two cephalosporins were readily eliminated from the blood after simultaneous administration: ca. 35% of the dose of cefotiam and 30% of the dose of cefsulodin was recovered in the dialysate over 5 h. These results suggest that the pharmacokinetics of the two drugs are not modified by their simultaneous administration and that the dosing schedule previously proposed for administration of the two cephalosporins alone in the presence of renal insufficiency can be applied without modification when they are given together. Patients on hemodialysis should receive a loading dose after each dialysis period, and then reduced doses according to recommendations for anuric patients.